Do chocalho ao bastão: processos educativos do terno de congado marinheiro de São Benedito Uberlândia-MG - Silva, Vívian Parreira da (Universidade Federal de São Carlos, 2011)
Based on studies about Popular Feasts it is possible to recognize different aspects which determine them as structuring practices on people s lives that experience those. It is still important to highlight that through these manifestations studies we are capable of knowing a little bit more about the Country s Popular Culture, not only as an entertainment or spectacle, but as something which is dynamized, modified, taking important part on group s and subject s identities formation. This paper had the objective to describe and analyze educational processes present in the Terno de Congado Marinheiro de São Benedito and, by this analysis, try to comprehend how these educational processes occur. The study was undertaken through a qualitative approach and the investigation strategy was a participative research. As for data collection, conversation circles were made and remarks about them registered on a field diary. There were two conversation circles containing five components each, from the Terno Marinheiro de São Benedito; collaborators of the research were aged between eleven and forty three years old. Guiding questions to conversation circles aimed to know: Terno s history, men and women s roles inside the group, teaching and learning relations and the importance to take part in a Congada group of the city. Analysis was divided in three phases: before-analysis, material exploration and treatment of obtained results and data interpretation. After detailed material perusals, it was listed the following thematic categories: 1 learn to life: orality, memories and experiences; 2 secrets and mysteries: visible and invisible worlds; 3 resistance, fight and prejudice; 4 collaboration and faith. Results showed that Congada is a social practice composed of educational processes involving elements such as collaboration and faith, fight, resistance, prejudice, relations between visible and invisible worlds and also learning for life. This social practice modifies daily life of its participants. Because of this Festivity, its sung music, ornaments, choreographies, different world opinions which compose the Congada pageants, congadeiros and congadeiras reaffirm their identity, show pleasure, joy and satisfaction by representing distinct roles from those of everyday life, keeping alive their tradition. This research indicates that congada in Uberlândia is a social practice which resists, transforms and educates. Because of that practice, men and women get formed to life creating strategies and diverse ways to be in the world, through dance, life histories, collaboration experiences and faith.
Keywords: Práticas sociais e processos educativos; Congada; Cultura popular; Social practices; Educational processes; Congada; Popular culture; CIENCIAS HUMANAS::EDUCACAO